The Impact of Long-Time Chemical Bonds in Mineral-Cement-Emulsion Mixtures on Stiffness Modulus - Bohdan Dołżycki; Mariusz Jaczewski; Cezary Szydłowski (The Baltic Journal of Road and Bridge Engineering)
Deep cold in-place recycling is the most popular method of reuse of existing old and deteriorated asphalt layers of road pavements. In Poland, in most cases, the Mineral-Cement-Emulsion mixture technology is used, but there are also applications combining foamed bitumen and cement. Mineral-Cement-Emulsion mixtures contain two different binding agents – cement as well as asphalt from the asphalt emulsion. Asphalt creates asphalt bonding (responsible for flexible behaviour), whereas cement generates hydraulic bonds (responsible for stiffness of the layer). Final properties of Mineral- Cement-Emulsion mixtures are a result of a combination of both binding agents. While the stiffness of the material is unaffected by asphalt bonding, an increase in stiffness with time is visible for materials treated with hydraulic binders. This publication presents the change in stiffness modulus of Mineral-Cement-Emulsion mixtures by Simple Performance Test. For the analysis, two batches of specimens were used: the first was tested 28 days after compaction (period stated in Polish recommendations) and the second was tested 1.5 years after compaction. Analysis showed that after 1.5 years the stiffness modulus increased by about 10% in comparison to the 28 days after compaction. The change is minor but still significant. Unexpectedly, the level of the increase was unaffected by the combination of the binding agents (asphalt emulsion, cement).